Hyperattenuated Lesions on Immediate Non-contrast CT After Endovascular Therapy Predict Intracranial Hemorrhage in Patients With Acute Ischemic Stroke: A Retrospective Propensity Matched Study - Han, Nannan; Zhang, Gejuan; Li, Yige; Ma, Haojun; Ge, Hanming; Zhang, Xiao; Zhao, Yong; Li, Shilin; Zhang, Leshi; Gao, Yanjun; Shi, Wenzhen; Yan, Peng; et al. (Frontiers in Neurology, 2021)
Background and Purpose: This study aimed to analyze the association between hyperattenuated lesions (HALs) and postoperative intracranial hemorrhage (IH) and predict perioperative IH through quantitative analysis of HALs in acute ischemic stroke (AIS) with anterior large vessel occlusion (LVO) after endovascular therapy (ET). Materials and Methods: This retrospective, propensity-matched study enrolled AIS who received ET from a single-center registry study between August 2017 and May 2020. The enrolled patients were divided into two groups: IH and non-IH, by follow-up postoperative CT. The occurrences of HALs on immediate CT after ET were also recorded. The association between IH and HALs after propensity score matching (PSM) was determined by binary logistic regression models. The receiver operating characteristic (ROC) curve was used to determine the predictive value of the highest CT Hounsfield units (HU) value on immediate CT. Results: Initially, 1,418 patients who underwent digital subtraction angiography were reviewed and 114 AIS patients with immediate postoperative CT and follow-up CT after ET were enrolled. Forty-nine out of the 114 patients developed IH after therapy. After PSM analysis, patients with IH were more likely to have HALs on immediate CT (Odds Ratio, OR 11.9, P = 0.002, and 95% CI: 2.485–57.284). For 80 patients with HALs, ROC analysis of the highest CT value in the HALs territory showed that the cut-off value was 97 HU, the sensitivity was 70.21%, and the specificity was 81.82%. Conclusions: Patients with HALs after ET are more likely to have perioperative IH. The highest CT value in the HALs area might be used to predict IH.